2004
DOI: 10.1242/jcs.01503
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication licensing in somatic and germ cells

Abstract: The DNA replication (or origin) licensing system ensures precise duplication of the genome in each cell cycle and is a powerful regulator of cell proliferation in metazoa. Studies in yeast, Drosophila melanogaster and Xenopus laevis have characterised the molecular machinery that constitutes the licensing system, but it remains to be determined how this important evolutionary conserved pathway is regulated in Homo sapiens. We have investigated regulation of the origin licensing factors Cdc6, Cdt1, Mcm2 and Gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 59 publications
6
77
0
2
Order By: Relevance
“…This fact could also explain why the blastoid and classical subtype had no significant difference in the MCM6 expression as a marker for the G1 arrest and not as a proliferation marker. As this cell cycle arrest has been shown by others Eward et al, 2004;Obermann et al, 2005;Tachibana et al, 2005), we could demonstrate that this has a clinical relevance in patients with MCLs. Our data on expression of repp86 in MCL (Schrader et al, 2005) showed that real proliferation activity is an important prognostic factor in MCL.…”
Section: Discussionsupporting
confidence: 79%
“…This fact could also explain why the blastoid and classical subtype had no significant difference in the MCM6 expression as a marker for the G1 arrest and not as a proliferation marker. As this cell cycle arrest has been shown by others Eward et al, 2004;Obermann et al, 2005;Tachibana et al, 2005), we could demonstrate that this has a clinical relevance in patients with MCLs. Our data on expression of repp86 in MCL (Schrader et al, 2005) showed that real proliferation activity is an important prognostic factor in MCL.…”
Section: Discussionsupporting
confidence: 79%
“…and are absent from the functional compartment [63] ( Figure 1A, B). The important role that repression of the licensing system plays in proliferation control is highlighted by the finding that Cdc6 over-expression sustains the proliferative capacity of differentiating cells [66].…”
Section: Gh Williams and K Stoebermentioning
confidence: 99%
“…Investigation of the DNA replication initiation machinery in different organisms, tissues and cell types has revealed that cell cycle withdrawal and loss of proliferative capacity are linked to a 'shut-down' of the licensing system [3,43,[62][63][64]. During the proliferation-differentiation switch, the MCM clamp loaders Cdc6 and Cdt1 are rapidly down-regulated as cells migrate from the transit amplifying compartment to the functionally differentiated compartment of self-renewing tissues.…”
Section: Defining the Proliferative Statementioning
confidence: 99%
See 2 more Smart Citations